From drowned drumlins to pyramid-shaped peaks: analysing the linguistic landscape of Geography to support English language learning in the mainstream classroom. Issue 4 (2nd October 2019) - Gallagher, Fiona; Leahy, Angela
Abstract : This article discusses ways in which subject teachers teaching through English can support the linguistic needs of learners whose first language is not English. It is argued that by focussing on the language of their particular discipline and adjusting their teaching in order to foreground language, subject teachers can make a significant contribution to addressing the language needs of these learners. The subject Geography has been chosen to illustrate ways in which this might be achieved. The topic of glaciation is explored from the perspective of language in order to highlight the complexity of the language used in Geography and to illustrate ways in which it can be made more accessible. Sample tasks that aim to engage learners simultaneously in new content (e.g. glacial erosion, deposition, landforms) as well as the language that is required to convey this content (to erode, to pluck, ablation, hydraulic) are presented. The linguistic features which are highlighted are drawn from two second-level Geography books that are currently used in Ireland. While the focus of the article is on Geography, the approach taken is of equal relevance to other subjects and can be used to support teaching in culturally and linguistically diverse classrooms.